اختبارات جذر الوحدة لبيانات البانل (اختبارات الجيل الأول) تطبيق على عينة من الدول النامية - العشعوش, أيمن (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to study the stationarity of panel data using the first-generation tests, including Levin Lin (LL), Im, Pesaram and Shin (IPS) and Wu and Maddala (WM). These tests are characterized by the presence of both sectional and temporal information content, leading to more accurate results with respect to stationarity. The first-generation tests are based on the assumption of independence between the sectional units (companies, states, etc.). To illustrate the mechanism of using the first generation tests, annual data for the period 2000 to 2011 were used for a group of 7 developing countries: Algeria, Tunisia, Morocco, Egypt, Mauritania, Iran and Syria. The data relate to a set of explanatory variables for economic growth. The results were very similar in terms of the presence or absence of the unit root. The parameters of the estimated fixed model corresponded to the economic theory. The results indicated a positive relationship between the growth rate of per capita real GDP and the investment variable as a percentage of GDP and Enrolled in secondary education and the index of openness to world trade, while the correlation between the dependent variable and the current government spending rate was reversed. يهدف هذا البحث إلى دراسة استقرارية بيانات البانل باستخدام اختبارات الجيل الأول، التي تشــــمل اختبار Levin Lin (LL) ، اختبار Im, Pesaram and Shin (IPS) واختبار Wu and Maddala (WM). تمتاز هذه الاختبارات بتطبيقها على بيانات ذات محتوى معلوماتي مقطعي وزمني معاً، للحصول على نتائج أكثر دقة فيما يتعلق بالاستقرارية. تستند اختبارات الجيل الأول على فرضية الاستقلالية بين الوحدات المقطعية (شركات أو دول أو غير ذلك). ولتوضيح آلية استخدام اختبارات الجيل الأول لجذر الوحدة لبيانات البانل، تم استخدام بيانات سنوية للفترة من عام 2000 إلى 2011 لمجموعة مكونة من 7 دول نامية هي: الجزائر، تونس، المغرب، مصر، موريتانيا، إيران وسورية. تتعلق البيانات بمجموعة من المتغيرات التفسيرية للنمو الاقتصادي. كانت النتائج متقاربة جداً من ناحية وجود أو عدم وجود جذر الوحدة، وقد توافقت معلمات نموذج التأثيرات الثابتة مع النظرية الاقتصادية، حيث أشارت النتائج إلى وجود علاقة موجبة بين معدل نمو نصيب الفرد من الناتج المحلي الإجمالي الحقيقي وكل من متغير الاستثمار كنسبة من الناتج المحلي الإجمالي ومتغير معدل عدد المسجلين في التعليم الثانوي ومؤشر الانفتاح للتجارة العالمية، بينما كانت العلاقة عكسية بين المتغير التابع ومعدل الإنفاق الحكومي الجاري.